Transcranial Magnetic Stimulation for the Treatment of Chronic Dizziness: A Randomized Controlled Trial in Bandung, Indonesia - Zahra Amir; Nabila Saraswati; Made Swastika; Zainal Abidin Hasan; Aisyah Andina Rasyid; Hasrita Soleiman; Bernadette Wilson (Sriwijaya Journal of Neurology, 2024)
Introduction: Chronic dizziness is a debilitating condition with limited treatment options. Transcranial magnetic stimulation (TMS) has shown promise in treating various neurological conditions. This randomized controlled trial investigated the efficacy and safety of TMS in treating chronic dizziness in Bandung, Indonesia. Methods: Participants with chronic dizziness (≥ 3 months) were randomly assigned to receive either active TMS or sham TMS for 10 sessions over two weeks. The active TMS group received 1 Hz stimulation over the right dorsolateral prefrontal cortex (DLPFC), while the sham group received placebo stimulation. The primary outcome was the change in Dizziness Handicap Inventory (DHI) score from baseline to four weeks post-intervention. Secondary outcomes included changes in Vertigo Symptom Scale (VSS) scores, Hospital Anxiety and Depression Scale (HADS) scores, and quality of life measures. Safety was assessed through monitoring of adverse events. Results: A total of 60 participants completed the study (30 in each group). The active TMS group showed a significantly greater improvement in DHI scores compared to the sham group (p < 0.001). Significant improvements were also observed in VSS, HADS, and quality of life measures in the active TMS group. No serious adverse events were reported. Conclusion: This study provides evidence for the efficacy and safety of TMS in treating chronic dizziness in the Indonesian population. TMS may be a valuable therapeutic option for patients with chronic dizziness who have not responded to conventional therapies.